Determination of the effect of ascorbic acid on the color of canned mushrooms (Volvariella volvacea) - Abeleda, Imelda M.; Gatchalian, Miflora M. (1973.)
The study was conducted to determine the effect of pretreatment and the addition of ascorbic acid on the color of canned mushrooms. Variables were method and length of blanching time, amount of ascorbic acid used, and the specific stage of addition of the ascorbic acid. The standard canning procedure followed was: washing and trimming of mushrooms at the "button" stage, blanching, filling into cans, addition of 2% brine, sealing, processing for 20 minutes at 250°F and finally, colling. There were 2 blanching methods employed: steam and plain water for 1, 2, 3, 4, 5 and 6 minutes. Best blanching time was determined by the proxidase test. The blanching procedure was replicated, making use of a third variable - .3% ascorbic acid solution. The effect of addition of ascorbic acid to the packing medium at reduced levels was also investigated, making use of objective and subjective tests. Results of the investigation indicated that the best pre-treatment was to blanch the mushrooms in a boiling .3% ascorbic acid solution for 4 minutes. This would ensure a better quality of canned mushrooms, color-wise. No unfavorable effect on the flavor and texture of the canned product was observed.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mushrooms, Canned